Effects of transcutaneous electrical nerve stimulation alone or as additional therapy on chronic post-stroke spasticity: systematic review and meta-analysis of randomized controlled trials. Issue 5 (27th February 2020) - Marcolino, Miriam Allein Zago; Hauck, Melina; Stein, Cinara; Schardong, Jociane; Pagnussat, Aline de Souza; Plentz, Rodrigo Della Méa
Abstract: Purpose: To evaluate the effects and to compare transcutaneous electrical nerve stimulation protocols, alone or as additional therapy in chronic post-stroke spasticity through a systematic review and meta-analysis of randomized clinical trials. Methods: Search was conducted in MEDLINE, Cochrane Library, EMBASE and Physiotherapy Evidence Database through November 2017 (CRD42015020146). Two independent reviewers performed articles selection, data extraction and methodological quality assessment using the Cochrane Collaboration's risk of bias tool. The main outcome was spasticity assessed with Modified Ashworth Scale or other valid scale. Meta-analysis was conducted using random effects method, and pooled-effect results are mean difference with 95% confidence interval. Results: Of 6506 articles identified, 10 studies with 360 subjects were included in the review. Transcutaneous electrical nerve stimulation alone or as additional therapy is superior to placebo TENS to reduce post-stroke spasticity assessed with Modified Ashworth Scale (−0.52 [−0.74 to −0.30] p  < 0.0001, 6 studies), especially in lower limbs (−0.58 [−0.82 to −0.34] p  < 0.0001, 5 studies), which is in accordance with the studies that used other scales. Low frequency TENS showed a slightly larger improvement than high-frequency, but without significant difference between subgroups. Most studies present low or unclear risk of bias. Conclusion: Transcutaneous electrical nerve stimulation can provide additional reduction in chronic post-stroke spasticity, mainly as additional therapy to physical interventions. Studies with better methodological quality and larger sample are needed to increase evidence power. Implications for Rehabilitation: Transcutaneous electrical nerve stimulation as additional treatment to physical interventions can lead to additional reduction in chronic post-stroke spasticity. High and low frequency transcutaneous electrical nerve stimulation showed similar results, with a smaller numerical superiority of low frequency TENS. More studies are needed to substantiate the best protocol of transcutaneous electrical nerve stimulation to the treatment of spasticity.